Survival of Ovarian Cancer Patients Is Independent of the Presence of DC and T Cell Subsets in Ascites - Wefers, Christina; Duiveman-de Boer, Tjitske; Yigit, Refika; Zusterzeel, Petra L. M.; van Altena, Anne M.; Massuger, Leon F. A. G.; De Vries, I. Jolanda M. (Frontiers in Immunology, 2019)
Tumor-infiltrating T lymphocytes are correlated with improved survival in ovarian cancer. A prominent feature of ovarian cancer is ascites, which could serve as liquid biopsy to assess the immune status of patients. To investigate whether immune cells in ascites are associated with patient outcome, we analyzed the amount of dendritic cell (DC) and T cell subsets in ascites from ovarian cancer patients diagnosed with high-grade serous cancer (HGSC). Ascites was collected from 62 HGSC patients prior to chemotherapy. Clinicopathological, histological and follow-up data from patients were collected. Ascites-derived immune cells were isolated using density-gradient centrifugation. The presence of myeloid DCs (BDCA-1+, BDCA-3+, CD16+), pDCs (CD123+BDCA-2+) and T cells (CD4+, CD8+) was analyzed using flowcytometry. Furthermore, the expression of co-stimulatory and co-inhibitory molecules on T cells and non-immune cells was assessed. Complete cytoreduction, response to primary treatment and chemosensitivity were associated with improved patient outcome. In contrast, immune cells in ascites did not significantly correlate with patient survival. However, we observed a trend towards improved outcome for patients having low percentages of CD4+ T cells. PD-1 was expressed by 30% of ascites-derived T cells and PD-L1 by 50% of non-immune cells. In contrast to tumor-infiltrating immune cells, the percentage of DC and T cell subsets in ascites was not directly correlated to the survival of HGSC patients. This indicates that ascites has a different immune environment than primary tumor tissue and that it cannot be used as liquid biopsy to assess the immune status of HGSC patients.